2014
DOI: 10.1152/ajpgi.00389.2012
|View full text |Cite
|
Sign up to set email alerts
|

Glugacon-like peptide-2: broad receptor expression, limited therapeutic effect on intestinal inflammation and novel role in liver regeneration

Abstract: The glucagon-like peptide 2 (GLP-2) is an intestinotrophic hormone with growth promoting and anti-inflammatory actions. However, the full biological functions of GLP-2 and the localization of its receptor (GLP-2R) remain controversial. Among cell lines tested, the expression of GLP-2R transcript was detected in human colonic myofibroblasts (CCD-18Co) and in primary culture of rat enteric nervous system but not in intestinal epithelial cell lines, lymphocytes, monocytes, or endothelial cells. Surprisingly, GLP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
58
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 51 publications
(67 reference statements)
8
58
0
1
Order By: Relevance
“…The discrepancy could be attributed to different species; however, caution should be taken in ruling out a glucagonotrophic role of GLP2 in mice. In fact, recent researches have demonstrated that GLP2R is more widely expressed than it was estimated (Angelone et al 2012, El-Jamal et al 2014. Therefore, it is necessary to explore the presence and localization of GLP2R in the pancreatic islets using validated GLP2R antibody and the opportune positive and negative controls to yield to conclusive results.…”
Section: Glp2 and Glycaemic Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…The discrepancy could be attributed to different species; however, caution should be taken in ruling out a glucagonotrophic role of GLP2 in mice. In fact, recent researches have demonstrated that GLP2R is more widely expressed than it was estimated (Angelone et al 2012, El-Jamal et al 2014. Therefore, it is necessary to explore the presence and localization of GLP2R in the pancreatic islets using validated GLP2R antibody and the opportune positive and negative controls to yield to conclusive results.…”
Section: Glp2 and Glycaemic Controlmentioning
confidence: 99%
“…It is well known that reduced adiposity could contribute to the preservation of insulin sensitivity because the adipose tissue has a considerable influence on systemic glucose homeostasis through secretion of adipocytokines (McArdle et al 2013). Interestingly, Glp2r mRNA expression has been detected in mouse mesenteric adipose tissue (El-Jamal et al 2014); however, its functional significance is still unknown. It is important to characterize whether GLP2 increases glucose incorporation in adipocytes when their response to insulin is impaired by obesity conditions.…”
Section: Mechanistic Insightmentioning
confidence: 99%
See 1 more Smart Citation
“…Since that time, numerous subtypes of endocrine cells within the intestinal mucosa and their peptide products have been characterized [2]. These enteric peptides have become the subject of intensive scientific investigation regarding regulation of their release [3][4][5], mechanisms of action [6][7][8], and diverse physiological effects, including those outside the digestive system such as bone [9], liver [10], lung [11], and the central nervous system [12][13][14]. This primarily was due to the discovery that enteric peptides, such as glucagon-like peptide 1 (GLP-1), gastric inhibitory peptide, and peptide YY, play key roles in the regulation of appetite, energy metabolism [15][16][17], and gut function [18][19][20], making them targets for managing prevalent human diseases of obesity and diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…The GLP-2R is expressed by myofibroblasts [26] and it was hypothesized that GLP-2 exerts its trophic actions indirectly through myofibroblasts as well. Indeed, GLP-2 signalling induces the release of several growth factors such us insulin-like growth factor-1 and keratinocyte growth factor, that are responsible for the proliferative effects of GLP-2.…”
Section: Introductionmentioning
confidence: 99%